Determination of the influence of the method of introducing C₆₀ fullerenes and functionalized carbon nanotube on the formation of the properties of aluminum alloy - Trenov, Mykola; Ponomarenko, Olga (Technology audit and production reserves, 2026)
The object of research is the influence of carbon nanotubes and fullerene nanomaterials C60 when introduced into the aluminum alloy AK12 on the formation of the eutectic microstructure. The problem solved during the research is the insufficient effectiveness of existing modifiers such as Sr, Na, TiC and SiC to improve silicon globularization, as well as the lack of simple and effective methods for introducing carbon nanomaterials. In the work, two methods for introducing carbon nanoparticles into the aluminum alloy were developed. Improved silicon globularization, mechanical and physical properties were achieved. The thickness of the silicon dendritic axis was reduced to almost 20–25 microns, the size of silicon inclusions was reduced from 2–10 microns, and the microhardness was increased almost twice, depending on the method. The improvement of properties is due to the fact that nanoparticles become centers of crystal nucleation and do not allow them to grow, which leads to a finer, more homogeneous structure of the alloy. Pre-treatment of nanomaterials allows them to be evenly distributed in the alloy, and the addition of magnesium improves the wetting properties. The features and distinctive features of the obtained results are that two technologically simple methods of introducing nanoparticles into the liquid AK12 alloy have been proposed, without the use of ultrasound. A significant improvement in the mechanical and physical properties of the alloy has been achieved compared to the reference AK12 alloy. Controlled grinding of the silicon structure has been ensured. Available materials and equipment, which are available in Ukraine and suitable for scaling up in industrial volumes, have been used. The modified AK12 alloy allows it to be used for the manufacture of castings of critical importance, such as pistons, transmission mechanisms, and engine housings.